Targeted mutagenesis in the silkworm Bombyx mori using zinc finger nuclease mRNA injection - Takasu, Yoko; Kobayashi, Isao; Beumer, Kelly; Uchino, Keiro; Sezutsu, Hideki; Sajwan, Suresh; Carroll, Dana; Tamura, Toshiki; Zurovec, Michal (Insect biochemistry and molecular biology, 2010)
Targeted mutagenesis is one of the key methods for functional gene analysis. A simplified variant of gene targeting uses direct microinjection of custom-designed Zinc Finger Nuclease (ZFN) mRNAs into Drosophila embryos. To evaluate the applicability of this method to gene targeting in another insect, we mutagenized the Bombyx mori epidermal color marker gene BmBLOS2, which controls the formation of uric acid granules in the larval epidermis. Our results revealed that ZFN mRNA injection is effective to induce somatic, as well as germline, mutations in a targeted gene by non-homologous end joining (NHEJ). The ZFN-induced NHEJ mutations lack end-filling and blunt ligation products, and include mainly 7 bp or longer deletions, as well as single nucleotide insertions. These observations suggest that the B. mori double-strand break repair system relies on microhomologies rather than on a canonical ligase IV-dependent mechanism. The frequency of germline mutants in G(1) was sufficient to be used for gene targeting relying on a screen based solely on molecular methods.
Keywords: deoxyribonukleasy; messenger RNA; DNA Breaks, Double-Stranded; dvouřetězcové zlomy DNA; genový targeting; oprava DNA; hmyzí proteiny; Zinc Fingers; zvířata; Bombyx; mutageneze; Deoxyribonucleases; DNA Repair; RNA, Messenger; bourec; Gene Targeting; Mutagenesis; Animals; Insect Proteins; zinkové prsty